Proteomic analysis of the interactome of glutamate receptors of the AMPA type : contactin associated protein 1 as a regulator of AMPA receptors - Santos, Sandra Manuela Domingues dos (2009)
Tese de doutoramento em Biologia (Biologia Molecular) apresentada à Fac. de Ciências e Tecnologia da Universidade de Coimbra